1999
DOI: 10.1046/j.1471-4159.1999.0720751.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Bound Acrolein

Abstract: Several lines of evidence support the role of oxidative stress, including increased lipid peroxidation, in the pathogenesis of Alzheimer's disease (AD). Lipid peroxidation generates various reactive aldehydes, such as 4-hydroxynonenal (HNE), which have been detected immunochemically in AD, particularly in neurofibrillary tangles, one of the major diagnostic lesions in AD brains. A recent study demonstrated that acrolein, the most reactive among the ␣,␤-unsaturated aldehyde products of lipid peroxidation, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 361 publications
(64 citation statements)
references
References 26 publications
2
61
0
1
Order By: Relevance
“…Acrolein is a product of lipid peroxidation (15,16) and is a biomarker that has been used to implicate oxidative damage in several diseases (17)(18)(19)(20). Immunohistochemical staining of the retinas of rd1 mice with an antibody that specifically recognizes acrolein showed faint staining at P18 (Fig.…”
Section: Increased Staining For a Marker Of Oxidative Damage In Conesmentioning
confidence: 99%
“…Acrolein is a product of lipid peroxidation (15,16) and is a biomarker that has been used to implicate oxidative damage in several diseases (17)(18)(19)(20). Immunohistochemical staining of the retinas of rd1 mice with an antibody that specifically recognizes acrolein showed faint staining at P18 (Fig.…”
Section: Increased Staining For a Marker Of Oxidative Damage In Conesmentioning
confidence: 99%
“…Acrolein-modified Protein-To investigate whether acrolein is produced in vivo, we previously raised mAb5F6 against acrolein-modified protein and demonstrated that acrolein was accumulated in the form covalently bound to proteins in vivo (10,16,17). In addition, based on the observations that the incubation of N ␣ -acetyllysine with acrolein predominantly generated FDP-lysine and that the antibody indeed recognized it, we regarded FDP-lysine as the epitope of the antibody (16).…”
Section: Identification Of Mp-lysine As the Major Epitope Of A Monoclmentioning
confidence: 99%
“…Immunohistochemical analysis of atheroscle-rotic lesions from a human aorta revealed that an acroleinderived epitope recognized by the antibody indeed constitutes the lesions in which intense positivity is associated primarily with macrophage-derived foam cells (16). In addition, Calingasan et al (17) have observed a strong immunoreactivity with mAb5F6 in the paired helical filament 1-labeled neurofibrillary tangles of Alzheimer's disease cases. Furthermore, utilizing an immunoassay system (18), the levels of protein-bound acrolein in human plasma have been recently determined, demonstrating that the extracellular concentrations of protein-bound acrolein in vivo could reach submillimolar ranges (19 -23).…”
mentioning
confidence: 97%
“…Brains of patients afflicted with Alzheimer's disease show abnormal expression of numerous oxidative stress indicators (1)(2)(3)(4)(5) as well as extensive evidence of oxidative damage to proteins (6) and nucleic acids (7,8). A prominent feature of the Alzheimer's disease brain is the widespread cerebral deposition of a 40 -43-amino acid peptide called the amyloid ␤-protein (A␤) 1 in the form of amyloid fibrils within senile plaques and in cerebral and meningeal blood vessels (9,10).…”
mentioning
confidence: 99%